The heart of McDonaldization: the perspective of the other. - Brimm, Morissa (2010)
This dissertation aims to investigate the effect of organisational culture change on job satisfaction and work motivation from the perspective of the employees. McDonald’s Restaurants have been chosen due to having embraced organisational change in the last five years. One particular branch has been chosen – Castle Marina McDonald’s, Nottingham – for analysis. Triangulation was used to collect the data needed for my research; methods used were both qualitative and quantitative to provide richer and more concrete data. A mix of interviews, participant observation, physical artefacts and company documents were used to enhance this study. All gathered information was collated and generated into a case study to provide readers with access to the narratives. The case study aimed to shed light on these key questions: To what extent does the theory of McDonaldization still hold resonance in its company of origin? To what extent has organisational change has facilitated a change in the degree of employee motivation at all levels of hierarchy? To what extent has the altering of McDonald’s organisational culture on paper had an impact in reality?